DESIGN OF WEST JAVA CULTURE LEARNING MEDIA BASED ON INTERACTIVE MULTIMEDIA FOR CILANDAK BARAT 08 SDN - Yasin Efendi; Sodikin Sodikin; Rizky Ramadhan (INFOKUM, 2022)
Science is developing rapidly enough to produce an innovation and new changes. Technology in the form of interactive multimedia is one of the impacts of current technological developments. Interactive multimedia is a communication method in which the output of the media comes from the input and participation of the user. Media still serves the same purpose but user input adds interaction and brings interesting features of the system for better enjoyment. In the form of an interface between the end user/audience and the media can be considered interactive. Interactive multimedia is not limited to electronic media or digital media. Board games, pop-up books, game books, flip books and constellation wheels are examples of printable interactive multimedia